(untitled) (Bangladesh Journal of Urology, 2020)
Objective : To compare the safety and efficacy of percutaneous nephrolithotomy (PCNL) and open surgery in the treatment of patients having large kidneystone (>2 cm ). Materials & Methods: This comparative study included 80 patients diagnosed with kidney stone disease admitted in the NIKDU during the period of Jan’ to Dec’2009 were divided conveniently into two groups. Intervention was done in the form PCNL(40) and open surgery (40). Clinical outcome like, perioperative complications,duration of surgery, mean hospital stay ,convalescence period, amount of analgesia required to relief pain, stone clearance rate were reviewed and compared between the groups. There was no significant difference in preoperative variables such as age,sex, stone size in cm, stone number- single/multiple and stag horn Stone. Results: There were statistically significant difference in the parameters between the groups,( PCNL vs opensurgery[mean ± SD]): duration of operation (min), 97.90±24.89 vs 136.62±23.54, postoperative hospitalstay (days) ,4.77 ± 3.98 vs 9.55 ± 3.65, mean time return to work (days), 3.09 ± 1.21vs 6.25 ± 1.53, ( p value is <0.001). Intraoperative complications like bleeding requiring blood transfusion are significantly lower in PCNL (11 cases 34.1%) than in open surgery( 18 cases 45.0%), (Chi-square = 4.82; p =0.049). The amount of analgesia required to relief pain was significantly reduced in PCNL vs open procedure (no patient required > 2 doses vs 27 patient required 3 or >3 doses ), p value is<0.001. The rate of stone clearance in percutaneous procedure,(25 cases,80%) is approaching to that of open procedure,(34 cases 85%), (p>0.05). Conclusion: PCNL is relatively safe& better treatment option than open surgery in the treatment of large renal calculi, It has almost similar stone free rate at discharge home but has definite advantages of lower morbidity, shorter convalescence and more rapid return to work. Bangladesh Journal of Urology, Vol. 16, No. 2, July 2013 p.51-56